2016
DOI: 10.3390/md14010015
|View full text |Cite
|
Sign up to set email alerts
|

The Oligo Fucoidan Inhibits Platelet-Derived Growth Factor-Stimulated Proliferation of Airway Smooth Muscle Cells

Abstract: In the pathogenesis of asthma, the proliferation of airway smooth muscle cells (ASMCs) is a key factor in airway remodeling and causes airway narrowing. In addition, ASMCs are also the effector cells of airway inflammation. Fucoidan extracted from marine brown algae polysaccharides has antiviral, antioxidant, antimicrobial, anticlotting, and anticancer properties; however, its effectiveness for asthma has not been elucidated thus far. Platelet-derived growth factor (PDGF)-treated primary ASMCs were cultured wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…ASMCs proliferation plays a key role in asthma airway remodeling and involves various signal transduction pathways and mediators, such as reactive oxygen species (ROS) and p38 mitogen-activated protein kinase (MAPK) [5, 6]. ROS can act as second messengers to regulate different signaling pathways, and they are important mediators of cellular proliferation [7].…”
Section: Introductionmentioning
confidence: 99%
“…ASMCs proliferation plays a key role in asthma airway remodeling and involves various signal transduction pathways and mediators, such as reactive oxygen species (ROS) and p38 mitogen-activated protein kinase (MAPK) [5, 6]. ROS can act as second messengers to regulate different signaling pathways, and they are important mediators of cellular proliferation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that fucoidan can improve allergic responses by regulating the immune response, including alterations in the Th1/Th2 balance, inhibiting the production of IgE, suppressing the degranulation of mast cells, and inhibiting the proliferation of ASM (23). At present, little has been done to explore on the use of fucoidan in allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of atopic allergic reactions with various fucoidan extracts improves allergic responses and prevents or reduces the symptoms of allergic disease by regulating the immune response, including an alteration in the Th1/Th2 balance, an inhibition of IgE production, and a suppression of mast cells degranulation (21,22). In our previous study, we found that oligo-fucoidan might reduce the proliferation of airway smooth muscle (ASM) cells (23). However, the effects of oligo-fucoidan on T cells during allergic disease remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of airway remodeling in asthma involves an increase of the ASM mass, potentially resulting from an increase of ASMC proliferation and a decrease of apoptosis. PDGFBB is a well‐known growth factor that stimulates the proliferation of ASMCs (Ito et al, ; Hirota et al, ; Yang et al, ). Interestingly, we observed that PDGFBB upregulated the expression of MIF, which has been reported to promote cell proliferation in several studies (Lacey et al, ; Guo et al, ; Xie and Xi, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, little information is available in the literature regarding a potential role of MIF in ASMCs, especially the effect of MIF on cell proliferation, migration, and apoptosis. Since it is well documented that platelet‐derived growth factor‐BB (PDGFBB) promotes the proliferation of ASMCs (Ito et al, ; Chen et al, ; Hirota et al, ; Yang et al, ), we first tested whether PDGFBB stimulates the expression of MIF. Then, we investigated the effects of MIF on proliferation, migration, and activation of ERK and focal adhesion kinase (FAK) in ASMCs infected with recombinant adenovirus containing wild‐type MIF cDNA (Ad‐MIF) or a green fluorescent protein (GFP)‐expressing adenovirus vector (Ad‐GFP) as a control virus.…”
Section: Introductionmentioning
confidence: 99%